TERRITORIAL INTEGRATION AND MARINAS IN SARDINIA - Sebastiano Curreli; Cheti Pira (European Regional Science Association (ERSA), 2011)
Nautical tourism, considered one of the elect expressions of Italy's offer in the field of tourism, assumes new strategic importance in Sardinia's economic and social framework in the light of the fallout it generates in terms of development and the multifaceted composition of the demand which today characterizes the sector. Such considerations are confirmed by the incidence of the fleet of pleasure craft compared to the resident population, although paradoxically the important marinas are present in areas that are marginal in the panorama of the region's holiday industry. This fact emphasizes the lack of correspondence between an important number of infrastructures - Sardinia is the second Italian region for port infrastructures and berths - and effective territorial integration between nautical installations and inland holiday resort structures. This is to say that it is still quite difficult to interpret the territorial effects of marinas on accommodation facilities.
Keywords: 330